Preliminary assessment of waste heat potential in major European industries - Panayiotou, Gregoris; Bianchi, Giuseppe; Georgiou, Giorgos S.; Aresti, Lazaros; Argyrou, Maria C.; Agathokleous, Rafaela; Tsamos, Konstantinos M.; Tassou, Savvas A.; Florides, Georgios A.; Kalogirou, Soteris A.; Christodoulides, Paul (My University, 2017)
Industrial processes are currently responsible for almost 26% of European primary energy consumptions (275 Mtoe/yr). Furthermore, most of the energy sources that drive the industrial sector are fossil fuel based. Every industrial process is characterised by a multitude of waste heat streams at different temperature levels whose recovery would undoubtedly contribute to the enhancement of the sustainability of the industrial sites and their products. Waste heat recovery systems can offer significant energy savings and substantial greenhouse gas emission reductions. For the latter to materialise technological improvements and innovations aimed at improving the energy efficiency of heat recovery equipment and reducing installation costs should take place. This paper outlines the opportunities and the potential for industrial heat recovery in the European Union by identifying and quantifying primary energy consumption in the major industrial sectors and their related waste streams and temperature levels. Through a systematic analysis considering waste heat and Carnot's potential estimation, detailed results are given for all industrial sectors, temperature ranges and EU countries. The 'big picture' is rather promising with regards to the estimated total waste heat potential.
Keywords: Carnot's potential; Energy statistics; Waste heat potential